Age Differences in Sexual Partners and Risk of HIV-1 Infection in Rural Uganda - Kelly, Robert J.; Gray, Ronald H.; Sewankambo, Nelson K.; Serwadda, David; Wabwire-Mangen, Fred; Lutalo, Tom; Wawer, Maria J. (JAIDS Journal of Acquired Immune Deficiency Syndromes, 2003)
Gender differentials in HIV prevalence and incidence among adolescents and young adults have been observed in studies from Uganda (Fig. 1) (1–4) and other sub- Saharan Africa countries (5–7). Female adolescents are, on average, eight times more likely to be HIV infected than male adolescents. Biologic mechanisms such as immaturity of the reproductive tract in younger women may increase susceptibility to HIV acquisition, and social and cultural practices that promote early sexual activity among women may also be important. Another hypothesized factor is that young women are infected by having sex with older men, who may be more likely to be infected (8–10). This assumption is supported by comparison of age-adjusted HIV prevalence data (4,5,11) and mathematic modeling (12,13). Few empiric studies have examined the effect of age differences between partners on the risk of HIV infection in young women, however (2,14,15). We undertook observational analyses of the sexual behavior characteristics of adolescents in Rakai District, Uganda, to assess the extent to which the age
Keywords: HIV; Adolescence; Sexual partners; Uganda.